Teaching: more than just lecturing - Roettger, C.; Roettger, L.; Walugembe, F. (Journal of University Teaching and Learning Practice, 2007)
This study focused on effective teaching strategies for university professors. The researchers studied the relationship between teaching effectiveness and the dynamics of student demographics. An examination of the changes in the composition of the college population over the last few decades, based on statistical data, as well as an overview of theories of teaching and learning published in professional books and journals in both K-12 and Higher Education, provided the framework for an assessment of the effectiveness of various approaches to teaching. The final recommendations are based on the conclusions resulting from a comprehensive analysis of various research studies.